Palladium Catalysts with Triglyme‐Functionalized NHC Ligands for Suzuki Coupling Reactions in Aqueous Solvent - Liu, Qingqing; Zhong, Jing; Tian, Funing; Wang, Qiwei; Wang, Yuanhua; Zhong, Liu; Huang, Qingfei (ChemistrySelect (Weinheim), 2021)
To perform green chemistry, hydrophilic catalysts with high activity and stability are required. We designed and synthesized a catalyst [Pd(IPr*TEG)(cin)Cl)] from commercially available materials; this catalyst could be used in a wide range of Suzuki coupling reactions in aqueous solvents. The reaction works smoothly under low catalyst loading with a good to excellent yield. It was noted that the catalyst can be recycled, and it performed well in cyclical reactions. A novel eco‐friendly catalyst [Pd(IPr*TEG)(cin)Cl)] from economical materials that could be used in a wide range of Suzuki coupling reactions in aqueous solvent.